ChemInform Abstract: Catalytic Epoxidation Activity of Keplerate Polyoxomolybdate Nanoball Toward Aqueous Suspension of Olefins under Mild Aerobic Conditions. Issue 49 (3rd December 2013) - Rezaeifard, Abdolreza; Haddad, Reza; Jafarpour, Maasoumeh; Hakimi, Mohammad
Abstract The catalytic efficiency of a sphere‐shaped nanosized polyoxomolybdate in the aerobic epoxidation of olefins in water is studied.